A Cross-Cultural and Linguistic Review of Thankfulness and Gratitude Expressions in Jordanian Arabic - Dr. Omar Hazaymeh, Dr. Monther Battah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Thankfulness and gratitude are used as politeness strategy to thank others and to show respect and admiration for what they do for those who need help or support. The present study aims at reviewing the thankfulness and gratitude expressions in Jordanian Arabic as a politeness strategy from a sociolinguistic point of view. The study shows the different types of thanking and gratitude expressions, their numeral structure, their linguistic formation and their semantics.